Social Media and Diplomacy: The Utilization of Instagram as An Instrument of Indonesia’s Economic Diplomacy - Yunita, Primadiana; Killian, PM Erza (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2024)
The Covid-19 pandemic has significantly transformed various aspects of interstate relations, including the practice of economic diplomacy. Traditional diplomatic methods, which relied heavily on direct interactions, have shifted toward digital approaches, including the use of social media. This research analyzes how the Indonesian government utilizes Instagram as a tool for economic diplomacy. The conceptual framework for this study is based on Kishan Rana’s three stages of economic diplomacy in developing countries: salesmanship, networking, and regulatory management (Rana, 2012). Employing a mixed-method approach that combines volume and thematic analysis, the study identifies several key findings. First, Indonesia’s economic diplomacy on Instagram is most active in Asia, with three accounts demonstrating the highest public engagement: the Indonesian embassies in South Korea, Kazakhstan, and Cambodia. In all cases, the involvement of private sectors, either within or in collaboration with the embassies, played a critical role. Second, an analysis of Instagram content patterns reveals that Indonesian representatives primarily focus on network-building activities, with minimal attention given to salesmanship and regulatory management. This indicates that the use of social media for economic diplomacy by Indonesian representatives remains largely an extension of Indonesia’s traditional diplomatic practices, which emphasize building and maintaining networks rather than pursuing broader economic objectives.